Applying an extended Health Policy Analysis framework to digitally mediated health system reform: Evidence from Saudi Arabia’s Health Sector Transformation Program - Ahmed Abdullah Alshehri; Asaad Abdulrahman Abduljawad (PLoS ONE, 2026)
Health policy analysis frameworks play a central role in understanding how reforms are designed, implemented, and experienced in practice. Walt and Gilson’s Health Policy Analysis Triangle has been widely used to examine the interaction between policy content, context, actors, and processes, particularly in settings where implementation is shaped by political and organizational dynamics. However, many contemporary health reforms are increasingly digitally mediated and culturally embedded, raising questions about whether existing frameworks sufficiently capture the conditions that structure implementation. This paper proposes a conceptual extension of the Health Policy Analysis Triangle by theorizing Technology and Culture as cross-cutting dimensions that shape how policy content is enacted through actors and processes within specific contexts. The extension is grounded in secondary analysis and theoretical interpretation of empirical patterns previously identified in an evaluation of Saudi Arabia’s Health Sector Transformation Program, a large-scale reform initiative implemented under Vision 2030. Drawing on previously collected policy documents and qualitative interview data from the doctoral study [6] SHSTP evaluation, the paper illustrates how digital infrastructure and sociocultural norms operate as structuring influences on coordination, accountability, participation, and patient-centred care. The proposed framework does not replace the original triangle but enhances its analytical adequacy for reforms unfolding in digitally mediated and culturally complex systems. By making Technology and Culture explicit, the extended model provides a pragmatic analytical framework for analyzing implementation variation and reform learning in Saudi Arabia, with potential relevance for other health systems undergoing rapid transformation when adapted to local contexts.